PEMANFAATAN WEBSITE INTERAKTIF DALAM RANGKA MEMPERMUDAH PENGENALAN DAN PENINGKATAN DAYA TARIK WISATA DI KABUPATEN BANTUL - Setyowati, Dwi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Nowadays, the fast technology development asked everyone who is able to pro-active in information technology, especially in information system development based on web. Information which is completed by visualization and animation can be easier understood by users. Interactive website is made to make easier the introduction and improvement of tourism interest in Bantul by using Macromedia Firework application program that is used for animation, programming language for PHP and data base server using MySQL ,Adobe Photoshop is used for picture editin. This interactive website is Bantul tourism communication media that based on web. It is able to make easier for all tourism stakeholders to know, to be familiar with, to understand data and Bantul tourism characteristics will be easy to be accessed by stakeholders or tuorists, both foreign and local tourists. The result of making website is to increase the numbers of tourists who visit to Bantul, this caused the increasing of society prosperity, especially society around tourist resort. The activities of tourism included souvenir, stall, special food, culture, transportation and labors